2016
DOI: 10.1186/s12891-016-1176-7
|View full text |Cite
|
Sign up to set email alerts
|

Peri-articular tranexamic acid injection in total knee arthroplasty: a randomized controlled trial

Abstract: BackgroundIntravenous tranexamic acid (IV TXA) is one of the most effective agents in use for reducing blood loss following total knee arthroplasty (TKA) but its safety regarding venous thromboembolic events (VTEs) remains in question. The direct, local application of TXA may reduce systemic toxicity whilst maintaining good or better bleeding control compared to IV TXA. The topical application of TXA via Hemovac drains has been reported previously with good results. However, there are no data on peri-articular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 27 publications
2
55
0
1
Order By: Relevance
“…[11] TXA can be administrated by several routes including topical, intravenous, oral, and intramuscular. [12] TXA can take about 2 hours for oral, 30 minutes for intramuscular, and 5 to 15 minutes for intravenous to achieve the maximum plasma concentration. [13,14] Thus, the best suitable method for rapidly increasing the therapeutic concentration of TXA is by the intravenous route.…”
Section: Methodsmentioning
confidence: 99%
“…[11] TXA can be administrated by several routes including topical, intravenous, oral, and intramuscular. [12] TXA can take about 2 hours for oral, 30 minutes for intramuscular, and 5 to 15 minutes for intravenous to achieve the maximum plasma concentration. [13,14] Thus, the best suitable method for rapidly increasing the therapeutic concentration of TXA is by the intravenous route.…”
Section: Methodsmentioning
confidence: 99%
“…previously cement was placed between the bone-cutting site and implant component to reduce bone oozing, and IAI of TXA was employed to reduce blood oozing after synovectomy. However, muscle oozing was not effectively managed using this approach, and the studies on IMI of TXA in unilateral TKA are limited [13][14][15]. Mao et al.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that IMI and IAI of TXA e ciently at reducing blood loss during TKA compared with a control group; but the difference between IMI and IAI was nonsigni cant [13]. Pinsornsak et al reported that the antibleeding effects of intramuscular injected and intravenous injected TXA were similar [14]. Yozawa et al reported that compared with placebo treatment, IMI of TXA was e cient at decreasing blood loss and drops in Hb and hematocrit [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard dosing ranged from 0.5 to 3 g for IV TA. Patients received a single 13,16,19,20,[22][23][24]26,27,31,[33][34][35][36][37][38][39][40][41]43,45 , double 12,17,21,24,25,30,35,44 , or triple 7,14,15,18,28 dosing of TA, depending on the study. Finally, the timing of IV administration differed amongst the reports.…”
Section: Discussionmentioning
confidence: 99%